Rotary systems for root canal gutta-percha removal: a review / Mohd Nazrin Mohd Isa, Nurul Ain Ramlan and Afzan Adilah Ayoub - Mohd Isa, Mohd Nazrin; Ramlan, Nurul Ain; Ayoub, Afzan Adilah (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Gaining a predictable outcome in endodontics is complicated by handling an endodontically treated. Compared to primary root canal therapy, non-surgical endodontic retreatment typically entails the removal of previous root filling materials. This process may be necessary to enable access to contaminated canal space for recleaning and to remove obturation materials that may have been contaminated by marginal penetration of microorganisms and microbial toxins. The achievement of patency at the canal terminus and the extension of cleaning as close as possible to the apical terminus have been identified as healing prognostic criteria. Gutta-percha (GP) is the current mainstay material utilised as an endodontic filling material, capable of performing comprehensive, three-dimensional sealing of the treated root canal system in a highly effective manner with considerable physical durability. Interestingly, since its initial discovery in the 17 th century, GP remains to this day the ideal obturation material used across, in essence, all dental clinics globally due to its material properties and versatility for use in conjunction with sealer compounds. The development of GP removal systems that can manage to remove GP in its entirety from root canals during non-surgical retreatment procedures is currently highly desirable for dental practices. This literature review investigated this current research niche and scrutinised two prevalently utilised rotary systems -Edgefile-XR and the XP-Endo shaper systems.